2021
DOI: 10.1371/journal.pone.0245542
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceptions of low risk behaviour and drivers to test for HIV among South African youth

Abstract: Human Immunodeficiency Virus (HIV) prevalence among South African youth is high, yet HIV testing remains suboptimal. We explored how perceptions of HIV risk and behaviours informed decisions to test for HIV. This study was conducted from April 2018 to March 2019 in Ekurhuleni district, Gauteng Province with males and females aged between 15–24 years. Twenty-five youth with unknown HIV status participated in in-depth interviews (IDIs); while four focus group discussions (FGDs) were conducted with those that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Another plausible reason for this could be the low-risk perception of being young and active and lacking physical signs of HIV. Young men who perceive their risk of HIV as low and do not have access to HIV testing services are less likely to have received an HIV test in their lifetime [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another plausible reason for this could be the low-risk perception of being young and active and lacking physical signs of HIV. Young men who perceive their risk of HIV as low and do not have access to HIV testing services are less likely to have received an HIV test in their lifetime [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible reason could be that young men have a low-risk perception and are unaware of the physical signs of HIV and its adverse consequences [53]. Evidence has shown that young men with low-risk perceptions who do not have access to HIV testing services are less likely to have received an HIV test in their lifetime [54,55]. Youth-friendly health services can help close the HIV testing gap among young men by addressing access barriers, providing a more accessible, equitable, and effective social environment, and linking to HIV treatment and care.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the low uptake of HIV testing services is a low HIV risk perception among adolescents (Muravha et al 2021). These low-risk perceptions among high school learners and the overall high incidence of HIV infection among AGYW underscore the importance of increasing usage and access to HIV prevention services provided in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of HIV prevention services for learners in high schools in South Africa, the uptake of HIV testing services among adolescents remains low (Lebina et al 2019 ). One of the reasons for the low uptake of HIV testing services is a low HIV risk perception among adolescents (Muravha et al 2021 ). These low-risk perceptions among high school learners and the overall high incidence of HIV infection among AGYW underscore the importance of increasing usage and access to HIV prevention services provided in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assessment of risk is challenging when reflecting on intimate relationships and in settings of intimate partner violence for instance, women might feel uncomfortable to discuss or acknowledge their own risk. The impact of these barriers is strongest in high-HIV prevalence settings, predominantly in eastern and southern Africa ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%